A randomized, double-blind, placebo-controlled trial investigating the effects of an Ocimum tenuiflorum (Holy Basil) extract (HolixerTM) on stress, mood, and sleep in adults experiencing stress - Lopresti, Adrian L.; Smith, Stephen J.; Metse, Alexandra P.; Drummond, Peter D. (Frontiers in Nutrition, 2022)
Background: In Ayurveda, Ocimum tenuiflorum (Holy Basil) is referred to as ‘the elixir of life’ and is believed to promote longevity and general wellbeing. Although limited, there are clinical trials to suggest Ocimum tenuiflorum has anti-stress effects. Purpose: Examine the effects of a standardized Ocimum tenuiflorum extract (HolizerTM) on subjective and objective measures of stress and sleep quality in adults experiencing stress. Study Design: Two-arm, parallel-group, 8-week, randomized, double-blind, placebo-controlled trial. Australian and New Zealand Clinical Trials Registry trial registration number ACTRN12621000609853. Methods: One hundred volunteers aged 18–65 years received either 125 mg of Ocimum tenuiflorum twice daily or a placebo. Outcome measures included the Perceived Stress Scale (PSS) (primary outcome measure), Profile of Mood States, Athens Insomnia Scale (AIS), Restorative Sleep Questionnaire, and the Patient-Reported Outcomes Measurement Information System-29. Sleep quality was also assessed using a wrist-worn sleep tracker (Fitbit), and stress changes were examined by measuring between-group differences in hair cortisol and stress responses after exposure to an experiment stress procedure known as the Maastricht Acute Stress Test (MAST). Results: Compared to the placebo, Ocimum tenuiflorum supplementation was associated with greater improvements in PSS (p = 0.09) and AIS (p = 0.025) scores; and at week 8, concentrations in hair cortisol were also lower (p = 0.025). Moreover, Ocimum tenuiflorum supplementation was associated with a buffered stress responses after exposure to the MAST as demonstrated by significantly lower concentrations in salivary cortisol (p = 0.001), salivary amylase (p = 0.001), systolic (p = 0.010) and diastolic (p = 0.025) blood pressure, and subjective stress ratings (p < 0.001). Ocimum tenuiflorum supplementation was well-tolerated with no reports of major adverse effects. Conclusion: The results from this trial suggest that 8 weeks of supplementation with an Ocimum tenuiflorum extract (HolizerTM) may reduce objective and subjective measures of stress, and improve subjective measures of sleep quality. However, further research using gold-standard objective sleep measures will be required to substantiate the sleep-related findings.